2001
DOI: 10.1051/hydro:2001002
|View full text |Cite
|
Sign up to set email alerts
|

Regards croisés sur l'état de la Loire Moyenne : potamoplancton et qualité de l'eau, quel enseignement tirer de 20 années d'études ?

Abstract: Résumé. -La Loire est utilisée par l'homme depuis très longtemps et c'est au début des années soixante qu'Electricité de France s'est préoccupée des nuisances que pouvait apporter la réfrigération de ses centrales thermiques. La mise en place de la Loi relative aux installations classées pour l'environnement, qui date de 1976, a conduit cet organisme à mettre en place des études de surveillance écologique du milieu. Les échantil-lons recueillis entre juin et octobre, de 1982 à 2001, ont permis de suivre les va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…The worsening eutrophication in the VB was the consequence of increasing DIN inputs from the Loire. A similar observation was reported in other coastal ecosystems, such as the Neuse River Estuary (Paerl et al, 2004), Belgian coastal waters (Lancelot et al, 2007) and the Seine Bay (Romero et al, 2013), where decreasing upstream Chl a, due to DIP input reduction, was accompanied by the increase in downstream Chl a, as a result of increasing DIN input. The seasonal change in annual Chl a peak in the VB also resulted from the conjunction of decreasing DIP loads and increasing summer DIN loads from the Loire.…”
Section: Link Between Eutrophication Trajectories In Rivers and In Thsupporting
confidence: 87%
See 3 more Smart Citations
“…The worsening eutrophication in the VB was the consequence of increasing DIN inputs from the Loire. A similar observation was reported in other coastal ecosystems, such as the Neuse River Estuary (Paerl et al, 2004), Belgian coastal waters (Lancelot et al, 2007) and the Seine Bay (Romero et al, 2013), where decreasing upstream Chl a, due to DIP input reduction, was accompanied by the increase in downstream Chl a, as a result of increasing DIN input. The seasonal change in annual Chl a peak in the VB also resulted from the conjunction of decreasing DIP loads and increasing summer DIN loads from the Loire.…”
Section: Link Between Eutrophication Trajectories In Rivers and In Thsupporting
confidence: 87%
“…This increase in summer DIN is the result of a delayed response due to the long transit time of DIN through soils and aquifers in the Loire catchment (up to 14 years; Bouraoui and Grizzetti, 2011). The decreasing DIN uptake by phytoplankton in the Loire may have also contributed to the increase in summer DIN (Lair, 2001;Floury et al, 2012). Concerning the Vilaine, the slight decrease in DIN from the early 1990s reflects the decrease in N fertilizer application in the Vilaine catchment (Bouraoui and Grizzetti, 2011;Aquilina et al, 2012), which is facilitated by a relatively short transit time of DIN in the Vilaine watershed (∼ 5-6 years; Molenat and Gascuel-Odoux, 2002;Aquilina et al, 2012).…”
Section: Eutrophication Trajectories At the River Basin Outletmentioning
confidence: 99%
See 2 more Smart Citations
“…This process, which generally follows a decrease in numbers of algae (Lair et al, 1999), has been shown to be also typical of several other temperate European rivers: the Mosel (Gosselain et al, 1998;Garnier et al, 1999), Rhine (Admiraal et al, , 1994de Ruyter van Steveninck et al, 1992), Seine (Garnier et al, 1995) and the Spree (Ko¨hler, 1993). In the Middle Loire, the appearance of this oxygen deficit was linked to the decrease of the algal density (associated with the increasing flow and the temperature drop) and the maintainence of abundant bacteria, which confirms the responsibility of the primary producers on the water oxygenation during the low water period (Lair & Reyes-Marchant, 2000;Lair, 2002). At the level of 4Ch, the oxygen deficit appeared two weeks later than at the three upstream sites, owing to tributaries fertilizer inputs and higher water temperature (20°C), which would preserve the algal development.…”
Section: Water Composition and Potamoplanktonmentioning
confidence: 63%